Translation Analysis of Cultural Terms Found in the Novel Ronggeng Dukuh Paruk by Ahmad Tohari and The Dancer by Rene T.A Lysloff and its Contribution to Cross Cultural Understanding Teaching - Setyani Tri Wahyu Briliyanti; Arso Setyaji; Indri Kustantinah (ETERNAL (English Teaching Journal), 2017)
The objectives of the study are (1) To categorize the cultural terms found in the novel Ronggeng Dukuh Parukinto The Dancer(2) To describe the techniques implemented in the translation of cultural terms in the novel Ronggeng Dukuh Parukinto The Dancer (3) To find out the contribution of novel Ronggeng Dukuh Paruk and The Dancer to Cross Cultural Understanding teaching.This is a descriptive research with qualitative analysis. The writer used following steps: (a) the writer read the novel Ronggeng Dukuh Paruk by Ahmad Tohari and its translation The Dancer by Rene T.A. Lysloff, (b) the writer search the cultural terms in the novel, (c) the writer analyzed the cultural terms found in the novel Ronggeng Dukuh Paruk and its translation The Dancer, (d) the writer analyzed the technique of translation, (e) the writer analyzed both of the novel to find out the possible contribution to Cross Cultural Understanding teaching. The result of this research are (1) Categories cultural terms found in the novel Ronggeng Dukuh Paruk and The Dancer. There are four categories of cultural terms related to Ronggeng Dukuh Paruk and The Dancer. Those are material culture, social culture, activities and procedures, and then gestures and habits. (2) technique implemneted in the translation of cultural terms in the novel Ronggeng Dukuh Paruk into The Dancer. In translation the novel, the translator applied borrowing technique i.e without any change the word of culture. (3) contribution of the novel Ronggeng Dukuh Paruk and The Dancer to Cross Cultural Understanding teaching. The contribution of translation analysis of cultural terms in the novel is giving information and developing the student’s knowledge. It also can be the new media of Cross Cultural Understanding teaching.